Dendrobine promotes bone formation via the canonical Wnt/β-catenin signaling pathway and prevents postmenopausal osteoporosis - Li, Shengfa; Liang, Peili; Chen, Jian; Zhang, Youming; Miao, Haixiong; Wang, Ting (Frontiers in Pharmacology, 2025)
BackgroundIn early postmenopausal women with sex steroid deficiency, an imbalance between bone resorption and bone formation causes an accelerated decline in bone mineral density due to a longer lifespan of osteoclasts and a shorter lifespan of osteoblasts. Given this context, dendrobine, as a primary bioactive alkaloid isolated from Dendrobium nobile Lindl., has potential efficacy on osteoporosis due to the traditional use of Dendrobium nobile Lindl. in musculoskeletal disease.ObjectiveTo investigate the anti-osteoporotic efficacy of dendrobine in increasing osteoblastogenesis and to elucidate the underlying mechanism.MethodsUsing C3H/10T1/2 cells and human bone marrow-derived mesenchymal stromal cells, the effects of dendrobine on osteoblastogenesis and underlying mechanism were assayed by Western blotting, alkaline phosphatase staining, and quantitative polymerase chain reaction. The effectiveness of dendrobine in preventing postmenopausal osteoporosis was assessed using an ovariectomized mouse model by micro-computed tomography, H&E, alkaline phosphatase, and immunohistochemical staining.ResultsIn addition to inducing alkaline phosphatase, Runx2, osteocalcin, and Osterix expression in C3H/10T1/2 cells or human bone marrow-derived mesenchymal stromal cells, Dendrobine increased Runx2, alkaline phosphatase, and osteocalcin expression in ovariectomy (OVX) mice.ConclusionIn OVX mice, dendrobine attenuated the loss of cancellous bone, as shown in micro-computed tomography analysis. Dendrobine activated the Wnt/β-catenin pathway by suppressing the phosphorylation level of GSK-3β at Tyr216 site while keeping the level of β-catenin sustaining. This study suggests that dendrobine may be an effective treatment for postmenopausal osteoporosis.